PENGEMBANGAN UMKM MELALUI SOSIALISASI BRANDING DAN PEMBUATAN SURAT IZIN USAHA PERDAGANGAN (SIUP) DI DESA JAYAMULYA - Al Ayubi, Salahudin; Ananto, Muhammad Yudo; Sulastri, Tuti; Rofieq, Ainur (An-Nizam, 2024)
MSME branding is very important when starting a business, so that it can increase sales and attract consumers by branding MSMEs by giving a meaningful logo, creating social media, creating a website for MSMEs so that they can be recognized by the public.  Non-governmental organizations are a reflection of the implementation of the Tridharma of Higher Education, especially in carrying out the point, namely community service. MSMEs activities obtain a trade business license. The benefit is to know in accordance with the original laws and regulations. In carrying out training in making trade business licenses. The way to implement community service is by conducting socialization to the community and direct training by delivering material containing training on trade business licenses for MSMEs. Community service activities in Jayamulya village, can provide education or understanding of the importance of business licenses, making it a real proof of selling entrepreneurship for the people of Jayamulya village. Another benefit of this socialization is that sellers have business licenses, brands and products sold with logo colors can be recognized by the public, so that they can maximize sales and display these products.